Lysolipids are prominent in subretinal drusenoid deposits, a high-risk phenotype in age-related macular degeneration - Anderson, David M. G.; Kotnala, Ankita; Migas, Lukasz G.; Patterson, N. Heath; Tideman, Léonore E. M.; Cao, Dongfeng; Adhikari, Bibek; Messinger, Jeffrey D.; Ach, Thomas; Tortorella, Sara; Van de Plas, Raf; Curcio, Christine A.; et al. (Frontiers in Ophthalmology, 2023)
Age related macular degeneration (AMD) causes legal blindness worldwide, with few therapeutic targets in early disease and no treatments for 80% of cases. Extracellular deposits, including drusen and subretinal drusenoid deposits (SDD; also called reticular pseudodrusen), disrupt cone and rod photoreceptor functions and strongly confer risk for advanced disease. Due to the differential cholesterol composition of drusen and SDD, lipid transfer and cycling between photoreceptors and support cells are candidate dysregulated pathways leading to deposit formation. The current study explores this hypothesis through a comprehensive lipid compositional analysis of SDD using highly sensitive tools of imaging mass spectrometry (IMS) and nano liquid chromatography tandem mass spectrometry (nLC-MS/MS), supplemented with transmission electron microscopy and immunohistochemistry. To elucidate mechanisms of deposit formation, an interpretable supervised machine learning approach was utilized to compare the lipid composition of SDD to regions of uninvolved retina across 1873 detected features and to automatically discern candidate markers for SDD. Three lipid classes, including lysophosphatidylcholine (LysoPC), lysophosphatidylethanolamine (LysoPE) and lysophosphatidic acid (LysoPA) were observed nearly exclusively in SDD while presumed precursors, including phosphatidylcholine (PC), phosphatidylethanolamine (PE) and phosphatidic acid (PA) lipids were detected in SDD and adjacent photoreceptor outer segments. Molecular signals specific to SDD were found in central retina and elsewhere. The abundance of lysolipids in SDD implicates lipid remodeling or degradation in deposit formation, consistent with ultrastructural evidence of electron dense lipid-containing structures distinct from photoreceptor outer segment disks and immunolocalization of secretory phospholipase A2 group 5 (PLA2G5) in photoreceptors and retinal pigment epithelium. Further studies are required to understand the role of lipid signals observed in and around SDD.